Radiographic Outcomes of Immobilization using Boston Brace for Pediatric Spondylolysis. (June 2021) - Virkki, E.; Holstila, M.; Mattila, K.; Pajulo, O.; Helenius, I.
Background and Aims: Spondylolysis is a common cause of lower back pain during youth. The aim of this study is to report the bony union rate and risk factors for non-union of the lumbar spondylolysis of pediatric patients treated with a rigid thoracolumbosacral orthosis (Boston brace). Materials and Methods: A retrospective review of 68 children (mean age = 13.9 years) treated for spondylolysis with a thoracolumbosacral orthosis. Patient charts and imaging studies were evaluated to identify the bony union rate of the spondylolysis after a minimum of 3 months of immobilization (mean = 4.2 months). Laterality, grade, level, and presence of high signal intensity in the magnetic resonance imaging were evaluated as prognostic factors. Results: Sixty-eight patients presented with 110 defects. Of them, 46 (42%) were incomplete fractures, 38 (35%) complete fractures, and 26 (24%) pseudoarthrosis. Of these defects, 38 (82.6%), 11 (28.9%), and 0 (0.0%) had bony union at the end of the treatment (p < 0.001). Unilateral defects healed significantly better than bilateral ones (relative risk = 1.71, 95% confidence interval = 1.16–2.54, 17/26 (65%) vs 32/84 (38%), p = 0.014). High signal intensity in the magnetic resonance images before the treatment predicted healing (relative risk = 13.24, 95% confidence interval = 1.93–91.01, 48/87 (55%) vs 1/24 (4.3%), p < 0.001). The level of the spondylolysis (L5 vs above L5) did not affect the healing rate. Conclusion: The union rates of spondylolysis with a thoracolumbosacral orthosis were similar as compared to earlier studies done with a low thoracolumbosacral orthosis. The grade of the defect, laterality, and presence of high signal intensity increased the probability of bony union. A high thoracolumbosacral orthosis (underarm) does not seem to improve the healing rate of pediatric spondylolysis defects.